Lean Hospital: Strategy of Operational Financing Efficiency in Supply Chain Management - Nihayatul Munaa; Lilis Ardini; Zufra Inayah (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
Health financing in Indonesia has increased from 27 US (2003) to 115 US (2017) and will continue to increase as the population increases. The JKN era is also a burden where health financing managed by BPJS is always deficit every year. Hospitals as health service providers must be able to carry out operational cost efficiency as mandated by the JKN era, namely quality control and cost control. One of the cost efficiency methods is the implementation of lean management in hospital operational processes, especially the supply chain management process (procurement, inventory control, distribution planning and demand management). This study aims to evaluate the improvement process and cost efficiency after the implementation of lean management in the supply chain management process at the hospital. This study used a single holistic case study method with the unit of analysis at the Lean team level at Panti Rapih Hospital, Yogyakarta. Research subjects are employees in the team who are directly involved in the implementation of lean management. Selection of research subjects based on purposive sampling. Total sample of 7 respondents for in-depth interview process. The research instrument used an interview guide. The result of this research is that lean management which is applied in the logistic unit of the neat orphanage hospital can reduce waste such as motion, inventory, and waiting time. In addition, another benefit that can be felt by management is increasing cost efficiency. The conclusion of this study is that lean management is recommended to be applied in health services such as hospitals.